Pre-Service Teachers Assisting the Transition of the Student with Autism from School to Adulthood - Burth, Jeanne Hager (Journal of the American Academy of Special Education Professionals, 2017)
Pre-service teachers, both Early Childhood Education majors and Secondary Education majors, were challenged through an assignment to plan and develop kits for learners with Autism Spectrum Disorder (ASD) to use in preparation for transitioning from school-age to work or independent or group home living. This Project-Based Learning (PBL) experience added relevance to the assignment and assisted pre-service teachers in understanding of the need for transitions. The goal of the study was to assess the pre-service teachers’ learning and understanding of the need for transitions for the students with exceptionalities by connecting learning to action with a PBL assignment. Since the assignment was authentic and would be used by students with ASD, pre-service teachers found more relevance and meaning to their learning than they may have with a traditional assignment. Also, by participating in this project, preservice teachers deepened their understanding of the student with ASD and became more confident in their own abilities to teach students with ASD. The practicing teachers, who are preparing students with ASD to transition from school to work or independent living, perceived the transition projects as desirable tools for teaching transition skills.